PENERAPAN MEDIA POP UP BOOK PADA PEMBELAJARAN PANCASILA MATERI NILAI NILAI PANCASILA KELAS IV - Tasya Amalia Dwi Ningrum; Apri Irianto (STKIP Subang, 2026)
This study examines the implementation of Pancasila Education Learning using Pop-Up book media for fourth-grade students at SDN Lambangan, with emphasis on Pancasila values content. The main aspects examined include the implementation of Pop-Up book media in learning activities, student engagement during the learning process, their responses to the use of this media, and obstacles encountered in its application. The methodology applied is a descriptive qualitative approach involving the School Principal, Fourth Grade Teacher, and fourth-grade students of SDN Lambangan as informants. Information collection was carried out through direct observation, structured dialogue, and review of related documents. Information analysis was conducted through stages of data simplification, information visualization, and conclusion formulation. The findings indicate that the application of Pop-Up book media significantly strengthens student engagement, learning enthusiasm, and activity during learning. The majority of students (88.1%) gave very positive appreciation to this learning media, indicating increased curiosity and enthusiasm for the learning substance. Pop-Up book media has proven successful in encouraging students to participate actively, especially in group discussion activities, and helps them appreciate Pancasila values more deeply. Nevertheless, this study also found several challenges in its implementation that need to be anticipated, particularly related to resource availability and the diversity of student learning styles. Thus, the use of this innovative media has great prospects for creating a more interactive and enjoyable learning atmosphere for students.